2013
DOI: 10.1152/ajpgi.00142.2012
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics prevent necrotizing enterocolitis by modulating enterocyte genes that regulate innate immune-mediated inflammation

Abstract: Necrotizing enterocolitis (NEC), an extensive intestinal inflammatory disease of premature infants, is caused, in part, by an excessive inflammatory response to initial bacterial colonization due to the immature expression of innate immune response genes. In a randomized placebo-controlled clinical trial, supplementation of very low birth weight infants with probiotics significantly reduced the incidence of NEC. The primary goal of this study was to determine whether secreted products of these two clinically e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
137
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(141 citation statements)
references
References 32 publications
3
137
0
1
Order By: Relevance
“…In studies from this laboratory (73), we have identified a secreted product from the same B. infantis which on partial characterization is likely a glycan of less than 30 kD size. This factor has an anti-inflammatory effect in a fetal small intestinal cell line (H4) and functions by causing a maturation of the innate inflammatory immune response to an inflammatory stimulus with a reduction in the expression of TLR-4, its signaling molecules and its transcription factor NFκB genes and an increase in negative regulators of this response (TOLLIP, SIGIIR, and A-20) as seen in mature enterocytes (73,74). Finally, a recent study of the molecular response of intestinal bacteria to breast vs. infant formula feeding has shown that the products of breastfed intestinal bacteria have a greater effect on protective genes in enterocytes than products of formula-fed infants (75).…”
Section: Breastfeeding and Intestinal Colonizationmentioning
confidence: 99%
“…In studies from this laboratory (73), we have identified a secreted product from the same B. infantis which on partial characterization is likely a glycan of less than 30 kD size. This factor has an anti-inflammatory effect in a fetal small intestinal cell line (H4) and functions by causing a maturation of the innate inflammatory immune response to an inflammatory stimulus with a reduction in the expression of TLR-4, its signaling molecules and its transcription factor NFκB genes and an increase in negative regulators of this response (TOLLIP, SIGIIR, and A-20) as seen in mature enterocytes (73,74). Finally, a recent study of the molecular response of intestinal bacteria to breast vs. infant formula feeding has shown that the products of breastfed intestinal bacteria have a greater effect on protective genes in enterocytes than products of formula-fed infants (75).…”
Section: Breastfeeding and Intestinal Colonizationmentioning
confidence: 99%
“…After all of the mice had been confirmed to be in a diabetic exerts effects on those pathways remains as yet unknown. The mixture of Bifidobacterium infantis and Lactobacillus acidophilus reportedly decreased the interleukin-6 (IL-6) mRNA level in primary intestinal epithelial cells isolated from resected ileum with necrotizing enterocolitis (11). Bifidobacteria longum significantly down-regulated levels of macrophage chemoattractant protein-1 (MCP-1) and IL-6 in porcine intestinal epithelial cells challenged with heatkilled enterotoxigenic Escherichia coli (34).…”
mentioning
confidence: 99%
“…There have been in vitro and animal studies as well as human clinical trials investigating the benefits of probiotics [22][23][24] ; however larger trials are necessary prior to recommending routine use in preterm infants [12,25,26] . There are recommendations for early initiation of enteral feeds and advancement of enteral feeds in accordance with evidence based feeding protocols [10,12] , promoting adequate intestinal motility and prevention of carbohydrate malabsorption.…”
Section: Discussionmentioning
confidence: 99%